Two new species of Plakina Schulze, 1880 (Porifera, Plakinidae) from the Aleutian Islands (Alaska, USA) - Lehnert, Helmut; Stone, Robert; Heimler, Wolfgang (Zootaxa, 2005)
Plakina tanaga and Plakina atka n. spp. are described from the waters around the Aleutian Islands at depths between 118 and 146m. These are the first records of the genus from the Aleutian Islands. The new species described here are compared with the six species of Plakina previously reported from the Pacific. Both species belong to the Plakina trilopha species-complex and differ from other Pacific species of Plakina in their conspicuous convoluted surface pattern, color, and spiculation. In addition to the usual set of triods both species have a second category with basally spined rays. Plakina tanaga n. sp. has a strongly convoluted, microtuberculate surface, and a few small, thin spines at the basal rays of the triods, and relatively large trilophose calthrops. Plakina atka n. sp. has a smoother surface, more numerous larger and thicker basal spines at the triods, and considerably smaller lophocalthrops which are tetralophate.